Coronavirus zoonozes associated with chiroptera - V. V. Makarov; D. A. Lozovoy (Ветеринария сегодня)
The paper considers natural historical aspects of emerging highly dangerous coronavirus infections found in a Chirocoptera reservoir, of serious acute respiratory syndrome ("atypical pneumonia") and Middle East respiratory syndrome, their origin and spread.